STUDY OF FORMER STREET KID RECEPTION TO MOVIE “ALANGKAH LUCUNYA NEGERI INI” - Agustian, Jaka Farih; Irawanto, Budi (Capture : Jurnal Seni Media Rekam, 2018)
Social problems in the aspect of street children in Indonesia is still difficult to solve. The Data 2017 issued by the Minister of Social Khofifah Indar Parawansa said there are 4.1 million Indonesian children who are displaced and need protection. Thus, various media attempts to provide criticisms about social conditions in Indonesia, especially through the construction of street children's films. Film of Alangkah Lucunya Negeri Ini describes social problems of street children happening in Indonesia. This study aims to explain how the reception of exformer street children in watching the film Alangkah Lucunya Negeri Ini using the method of reception proposed by Stuart Hall, namely the concept of dominant hegemony, negotiation, and opposition. The results show that informant receptions arise due to different social and cultural dimensions in life as street children in the past. The informants also made the film Alangkah Lucunya Negeri Ini as reflection based on life experience. Thus, the presence of the film gives negative stigma of street children in social relations of society. Scene of film also brings the informant to feel the pleasure of watching that is expressed through both entertaining and emotional forms. Meanwhile, audience also responded activelly to the construction of street children films in social, educational, and religious discourse. Informants who are in the dominant code express their interest in film programs motivated by behavior and social experience as street children. While informants who are in a negotiating position try to be adaptive in adjusting the message in the film, but also have an attitude of opposition as a form of rejection. While the informants who placed themselves in the opposition expressed a different attitude to the construction offered in the film program. There is an element of discomfort with the presence of street children movies in their lives.